A Prospective Cohort Study on the Prevalent and Recurrent Tuberculosis Isolates Using the MIRU-VNTR Typing - Qiu, Beibei; Tao, Bilin; Liu, Qiao; Li, Zhongqi; Song, Huan; Tian, Dan; Wu, Jizhou; Wu, Zhuchao; Zhan, Mengyao; Lu, Wei; Wang, Jianming (Frontiers in Medicine, 2021)
The study aims to describe the clustering characteristics of mycobacterium tuberculosis (M.tb) strains circulating in eastern China and determine the ratio of relapse and reinfection in recurrent patients. We recruited sputum smear-positive pulmonary tuberculosis cases from five cities of Jiangsu Province, China, during August 2013 and December 2015. Patients were followed for the treatment outcomes and recurrence based on a cohort design. M.tb strains were isolated and genotyped using the 12-locus MIRU-VNTR. The Beijing family was identified by the extended Region of Difference (RD) analysis. The Hunter-Gaston Discriminatory Index (HGDI) was used to judge the resolution ability of MIRU-VNTR. The odds ratio (OR) together with 95% confidence interval (CI) were used to estimate the strength of association. We performed a cluster analysis on 2098 M.tb isolates and classified them into 545 genotypes and five categories (Ⅰ, 0.19%; Ⅱ, 0.43%; Ⅲ, 3.34%; Ⅳ, 77.46%; Ⅴ, 18.59%). After adjusting for potential confounders, the Beijing family genotype (OR=118.63, 95% CI: 79.61-176.79, P=0.001) was significantly related to the dominant strain infections. Patients infected with nondominant strains had a higher risk of the pulmonary cavity (OR=1.39, 95% CI: 1.01-1.91, P=0.046). Among 37 paired recurrent cases, 22 (59.46%) were determined as endogenous reactivation, and 15 (40.54%) were exogenous reinfection. The type of M.tb strains prevalent in Jiangsu Province is relatively single. Beijing family strains infection is dominant in local tuberculosis cases. Endogenous reactivation appears to be a major cause of recurrent tuberculosis in Eastern China. This finding emphasizes the importance of case follow-up and monitoring after the completion of antituberculosis treatment.